60 Maximising injury research through translation of an evidence-based safe teen driving program into a workplace wellness program. (9th June 2015) - Harland, Karisa; Roth, Lisa; Peek-Asa, Corinne
Abstract : Statement of purpose: Previous intervention studies have demonstrated that increasing parent involvement in teen driving increases safe driving behaviour. The purpose of this research is to translate an evidence-based safe teen driving program into a workplace wellness program. Methods: Steering Teens Safe (STS), an evidence-based teen driving intervention, involves training parents in effective communication before/during their teens intermediate licensing. STS is currently being translated into workplace wellness programs. To increase translation effectiveness, the Replicating Effective Programs framework and the RE-AIM model are being applied. Parent-employees completed a focus group to identify facilitators and barriers to translation. STS was modified into a 3-month program where parent-employees receive three one-hour trainings on communication, complete online tutorials and answer three surveys (baseline, 1-month, and 3-months). Results: Facilitators to translation included a parents desire to teach their child, a child's desire to want to drive, and a culture of safety and wellness within the business. Barriers identified by parents were time and a teen's potential response to this new type of communication. Three businesses are currently enrolled in STS and the majority of the STS communication trainings have been facilitated by a trainer within each business. To date, 27 parent-employees (8 fathers, 19 mothers) have completed the wellness program. From baseline to the 3-month follow-up, parent-teen communication improved significantly (p = 0.04). The most frequently completed online tutorials focused on basic safety principals of taking driving seriously (72%), always wearing your seatbelt (68%) and avoiding distractions while driving (68%). Of interest, the least completed tutorials were on setting guidelines for your child to drive (40%). Conclusion: Injury research can be effectively translated into a workplace. Parent-teen communication about driving improved following translation of an evidence-based intervention into a wellness program. Further translation of evidence-based programs is needed to maximise the benefits of injury research.